2019
DOI: 10.1186/s13104-019-4192-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of road traffic injury and potential consequences among patients visiting Hawassa University Comprehensive Specialized Hospital, Hawassa, Ethiopia

Abstract: Objective Road traffic injury (RTI) is the leading cause of death among aged 15–29 years, although low and middle income countries only have half of the vehicles, they have 80% of road traffic related death. This study aimed to assess the probability of road traffic injury occurrence and potential consequences among patient visiting at emergency department of Hawassa University Comprehensive Specialized Hospital, Hawassa, Ethiopia. Retrospective cross-sectional study was conducted from March 8 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…In our study, we found over-speeding (reported by more than 60% of the participants) to be the key contributing reason behind accidents. A similar study from Ethiopia reported a congruent result as they mentioned high speed (reported by 48.9% injured patients) to be the leading cause behind accident [ 35 ].…”
Section: Discussionmentioning
confidence: 92%
“…In our study, we found over-speeding (reported by more than 60% of the participants) to be the key contributing reason behind accidents. A similar study from Ethiopia reported a congruent result as they mentioned high speed (reported by 48.9% injured patients) to be the leading cause behind accident [ 35 ].…”
Section: Discussionmentioning
confidence: 92%
“…3 Considering the intent of trauma, 159 (75.4%) of the admissions were due to unintentional injury which is in agreement with the result of a systemic review done by Azaj et al 4 RTC was the leading cause of trauma admissions and was nearly the same with the result of a study done at Hawassa University Comprehensive Specialized Hospital which was 40.9%. 14 According to Kirya et al, RTC was the leading cause of trauma admissions that accounted for 75%. 16 This could be attributed to the geographic difference and concentration of vehicles to larger cities in low and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…The emergency department of the hospital provides services to 102,033 patients a year. In addition, this unit serves 1800 injured patients a year, including 960 head injuries [ 18 ].…”
Section: Methodsmentioning
confidence: 99%